Effect of multiple impeller designs and configurations on the droplet size and uniformity in a 100 L scale stirred tank - Park, Jeil; Ahan, Wooyoul; Lee, Jae W. (The Korean journal of chemical engineering, 2021)
This study investigated the effect of multiple impeller designs and configurations on the Sauter mean diameter and the uniformity of droplet size in a 100 L scale stirred tank. By using a borescope installed inside the tank, droplet images of a highly turbid liquid-liquid system were captured even at high impeller speeds, and by adjusting the borescope position, it could be observed how the droplet size changed depending on the position. The area of the flow pattern produced by the impeller was taken as an impeller region, and it explained well the change in the droplet size due to the varying liquid phase volume and impeller spacing. In addition, the change of the Sauter mean diameter and the droplet size uniformity was also elucidated by the variation of the impeller diameter, blade angle, and number of impellers. All three parameters showed a decrease in the deviation between droplet sizes as they increased, but increasing the impeller diameter was the most effective in reducing the Sauter mean diameter itself.